Collective action for knowledge mobilisation: a realist evaluation of the Collaborations for Leadership in Applied Health Research and Care - Jo Rycroft-Malone; Christopher Burton; Joyce Wilkinson; Gill Harvey; Brendan McCormack; Richard Baker; Sue Dopson; Ian Graham; Sophie Staniszewska; Carl Thompson; Steven Ariss; Lucy Melville-Richards; et al. (National Institute for Health Research, 2015)
Background: The establishment of the Collaborations for Leadership in Applied Health Research and Care (CLAHRCs) was the culmination of a number of policy initiatives to bridge the gap between evidence and practice. CLAHRCs were created and funded to facilitate development of partnerships and connect the worlds of academia and practice in an effort to improve patient outcomes through the conduct and application of applied health research. Objectives: Our starting point was to test the theory that bringing higher education institutions and health-care organisations closer together catalyses knowledge mobilisation. The overall purpose was to develop explanatory theory regarding implementation through CLAHRCs and answer the question 'what works, for whom, why and in what circumstances?'. The study objectives focused on identifying and tracking implementation mechanisms and processes over time; determining what influences whether or not and how research is used in CLAHRCs; investigating the role played by boundary objects in the success or failure of implementation; and determining whether or not and how CLAHRCs develop and sustain interactions and communities of practice. Methods: This study was a longitudinal realist evaluation using multiple qualitative case studies, incorporating stakeholder engagement and formative feedback. Three CLAHRCs were studied in depth over four rounds of data collection through a process of hypothesis generation, refining, testing and programme theory specification. Data collection included interviews, observation, documents, feedback sessions and an interpretive forum. Findings: Knowledge mobilisation in CLAHRCs was a function of a number of interconnected issues that provided more or less conducive conditions for collective action. The potential of CLAHRCs to close the metaphorical 'know-do' gap was dependent on historical regional relationships, their approach to engaging different communities, their architectures, what priorities were set and how, and providing additional resources for implementation, including investment in roles and activities to bridge and broker boundaries. Additionally, we observed a balance towards conducting research rather than implementing it. Key mechanisms of interpretations of collaborative action, opportunities for connectivity, facilitation, motivation, review and reflection, and unlocking barriers/releasing potential were important to the processes and outcomes of CLAHRCs. These mechanisms operated in different contexts including stakeholders' positioning, or 'where they were coming from', governance arrangements, availability of resources, competing drivers, receptiveness to learning and evaluation, and alignment of structures, positions and resources. Preceding conditions influenced the course and journey of the CLAHRCs in a path-dependent way. We observed them evolving over time and their development led to the accumulation of different types of impacts, from those that were conceptual to, later in their life cycle, those that were more direct. Conclusions: Most studies of implementation focus on researching one-off projects, so a strength of this study was in researching a systems approach to knowledge mobilisation over time. Although CLAHRC-like approaches show promise, realising their full potential will require a longer and more sustained focus on relationship building, resource allocation and, in some cases, culture change. This reinforces the point that research implementation within a CLAHRC model is a long-term investment and one that is set within a life cycle of organisational collaboration. Funding: The National Institute for Health Research Health Services and Delivery Research programme.